Design and processing of near-β Ti–Nb–Ag alloy with low elastic modulus and enhanced corrosion resistance for orthopedic implants - M.A. Hussein; M.A. Azeem; A. Madhan Kumar; S. Saravanan; N. Ankah; A.A. Sorour (Journal of Materials Research and Technology, 2023)
This research aims to design and process a low elastic modulus near -β Ti–30Nb–3Ag at% (TNA) alloy with enhanced corrosion and antibacterial characteristics for bioimplant uses. Powder metallurgy was used to process the TNA alloy, which was designed via a combined approach of molybdenum equivalency and the d-electron alloy design method. The alloy powder samples were sintered at 1100, 1200, and 1300 °C. XRD and SEM were utilized to examine the phases and microstructure. The modulus of elasticity and microhardness were evaluated using microindentation. The in vitro corrosion properties were also examined in artificial body fluid medium. The results showed that TNA alloy was predominantly composed of β-Ti, with trace amounts of α-Ti, α’’, and Ti2Ag phases. The density and microhardness were increased by increasing the sintering temperature, and the sample sintered at 1300 °C exhibited a homogeneous microstructure with 89.7% densification. The modulus of elasticity of the designed TNA alloys lowered by (28.5–43) % and (24–38) % compared to Ti6Al4V alloy and CP-Ti, respectively, which potentially contributes to a decrease in the stress-shielding effect. The in vitro corrosion results indicated that the resistance to corrosion of the TNA alloy improved with increasing sintering temperature as evidenced by an increase in charge transfer resistance, noble corrosion potential, and passive current density. Furthermore, the TNA alloy also demonstrated a higher antibacterial capability (82.9%) compared to Ti6Al4V alloy. The designed TNA alloy with low elastic modulus exhibits higher in vitro corrosion resistance and antibacterial properties making it a potential bioimplant material.